Lineament Geomorphologic Analysis to Identify Fault in Mount Semeru, East Java - Dian Pratiwi Malik; Sukir Maryanto; Alamsyah Mohammad Juwono (Postgraduate, University of Mataram, 2023)
This research analyzes the morphological lineaments on Mount Semeru, East Java. The morphological lineament is processed using satellite imagery as a digital elevation model (DEM), downloaded on the Badan Informasi Geospasial (BIG) page. The image was processed using Global Mapper software with azimuth angles of 00, 450, 900, 1800, and 3150 and produced a lineament map that had been overlaid from all azimuth angles and created a morphological lineament map with various groups of values from high to low. From the analysis that has been carried out, it was found that there are 103 lineaments, most of which are spread in the area west of the crater of Mount Semeru, with the dominant direction showing a west-southwest – east-northeast orientation.